Development of a virtual-reality eye movements-based system to assess basketball players` decision making - Jia, Y.; Zhou, X.; Tang, Y.; Li, Q.; Wang, J.; Fu, Q. (Perceptual and Motor Skills, 2025)
Background and Purpose: This study developed a reliable and ecologically valid virtual reality eye movements-based assessment system to evaluate basketball players` decision-making abilities.